BORNEO AS A GOLDEN CHARIOT TO LOVE NATURE IN DIALECTICAL PERSPECTIVE - Sumardjo; Rosmiati (Fakultas Ilmu Budaya, Universitas Mulawarman, 2019)
Borneo as a Golden Chariot is created to be the medium for dialectics about a wealthy heritage in the plane of humanity full with Dayak life’s story that offers attractiveness to be scientifically investigated. This land is used to be the vehicle of a spiritual journey to unfold the milestone of Dayak tribes in the literary frame. The journey is expected to meet the horizon of expectation to love wisdom in the air of refreshment of mind namely a theatrical logics. Karrie Rayun Lampan as a Dayak poet sculpts the tree of Dayak’s life within a poetic rhetoric in the garden of a social art. He propounds his poetic rhetoric with the theme ‘Dayak spreads over in many places but retains nowhere’ in the word of this paper ‘somewhere between home and land, not home and water.’ For the poet, Borneo is as the homelandofaliterarygardenenabletopenetrateahumansensibility. This issue is directed to investigate dialectical perspective to the substitution of master tropes such as metaphor, metonymy, synechdoche, and irony onto a practical act, symbolic art, attitude and externalization of attitude, and dialectics respectively. This inve stigation concludes that the dialectics as probable argument to launch the opinions in the rational reasoning among the a practical act of daily activity of Dayak and its creation can be used as the formation of idea on the sensibility toward a literary world and the attitude and externalization of attitude should be brought to the higher order of thinking, those are analysis, evaluation, and creation instead of being in the state of being in the low order thinking as in remembrance, understanding and practicing only. And in order to fulfill the love of wisdom, the symbolic action is committed to promote for the happiness for all and continuously holds to the refreshment of mind.